Adopting cultural intelligence strategies for the silver craftsmen - Kusumawijaya, Ida Ketut; Astuti, Partiwi Dwi; Wartana, I Made Hedy; Adi, I Ketut Yudana (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2025)
The silvercrafting tradition in Kamasan Village, Klungkung, Bali, faces significant challenges, including declining youth participation, restricted market access, and limited cultural adaptability. This community service initiative aimed to empower silver craftsmen by integrating cultural intelligence strategies to enhance their global competitiveness while preserving traditional craftsmanship. The program focused on developing metacognitive, cognitive, motivational, and behavioral competencies to strengthen market adaptability and innovation. A participatory action community service framework guided the initiative for 34 silver craftsmen, structured into three phases: a pre-test to assess cultural intelligence baseline, targeted capacity-building workshops, and a post-test to evaluate progress. The training incorporated scenario-based activities, knowledge-sharing sessions, motivational discussions, and role-playing exercises to enhance cross-cultural adaptability. Findings revealed significant improvements in all cultural intelligence dimensions, with the overall mean score rising in post-intervention. The behavioral dimension exhibited the highest gains, particularly in verbal and non-verbal communication skills. However, challenges such as gender disparities and low youth engagement underscored the need for inclusive strategies. This initiative demonstrated the transformative potential of cultural intelligence training in sustaining traditional industries, reinforcing cultural identity, and fostering market expansion. Future programs should focus on long-term sustainability through mentorship, digital engagement, and targeted inclusivity efforts.